Comparative Label-Free Quantitative Proteomics Analysis Reveals the Essential Roles of N-Glycans in Salt Tolerance by Modulating Protein Abundance in Arabidopsis - Liu, Chuanfa; Niu, Guanting; Li, Xiaowen; Zhang, Huchen; Chen, Huawei; Hou, Dongxia; Lan, Ping; Hong, Zhi (Frontiers in Plant Science, 2021)
Many evidences show that the adaptive response of plants to salt stress requires the maturation of N-glycan on associated proteins. However, it is still little known about the salt responsive glycoproteins that function in this process. In the present study, we identified salt responsive glycoproteins in wild-type Arabidopsis (WT) and two mutants defective in N-glycan maturation, mns1 mns2 and cgl1. A total of 97 proteins with abundance changes of > 1.5- or < 0.67-fold were identified against salt stress by label-free LC-MS/MS quantitative analyses. A comparison of differentially abundant glycoproteins (DAGs) indicated the substrate preferences regulated by MNS1/MNS2 and CGL1. In addition, the DAGs in mns1 mns2 hardly form functional regulatory networks in STRING analysis. Comparably, the regulatory network in cgl1 was visible and shared overlapping with that in WT. Such difference may supply the evidence to partially explain the lower salt sensitivity of mutant cgl1 than mns1 mns2. We further confirmed that two N-glycosylation clients, peroxidases PRX32 and PRX34, were involved in the salt stress response since the double mutants showed the enhanced salt sensitivity. Together, our study provided proteomic evidence that N-glycans are crucial for modulating stress responsive protein levels, and several novel glycoproteins responsible for salt stress tolerance in Arabidopsis were listed. Data are available via ProteomeXchange with identifier PXD006893.